Semiotic Analysis of the Poem "If the People One Day Will to Live" (المجلة الدولية للبحوث العلمية, 2025)
This study is a semiotic analysis of the poem "If the People One Day Desire Life" by the poet Abu al-Qasim al-Shabi. The text is analyzed through the semiotic approach to examine its symbolic and semantic structure. The study aims to understand how al-Shabi uses linguistic signs and symbols to convey revolutionary and liberatory meanings, while also linking these symbols to their cultural, political, and social contexts.The study addresses several semiotic factors that contribute to conveying the revolutionary message in the poem, including subjective factors (the poet himself), the main theme (freedom), and the desired theme (liberation from colonialism). The analysis also covers opposing factors such as tyranny, as well as supportive factors such as the people's will, which emerges as the driving force behind achieving social and political change.The study reveals that the poet uses the poem as a tool to express the collective consciousness of the oppressed Arab people, relying on language as a means to convey liberatory ideas aimed at stimulating revolutionary action against tyranny and occupation. The study also highlights that the poem is not merely an expression of a specific political moment, but a symbolic text full of universal meanings that transcend time and place, requiring the reconstruction of the collective identity of the Arab nations in confronting political and social challenges.The study concludes with several recommendations, the most important of which is expanding the use of the semiotic approach in Arabic literature.